IMPLEMENTATION OF CASE-BASED LEARNING AND PROJECT-BASED LEARNING MODELS ASSISTED BY ARTIFICIAL INTELLIGENCE TECHNOLOGY TO IMPROVE STUDENT LEARNING OUTCOMES AND PARTICIPATION - Kuntarto, Eko; Noviyanti, Silvina; Ismiatun, Asih Nur; Bisri, Muawan (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study applies case-based learning and project-based learning models assisted by artificial intelligence technology with the aim of realizing differentiated learning, improving learning outcomes, and student participation. This study uses a Quasi Experimental design, with five main steps, namely: Preliminary Study, Preparation of Research Design, Technology Implementation, Data Collection, Data Analysis, and Interpretation of Results. The subjects of the study were 159 students of the Elementary School Teacher Education Study Program in semester 1 who took the Indonesian Language course. Data were obtained through observation, formative evaluation, summative evaluation, student satisfaction surveys, and questionnaires. Based on the correlation analysis of the results of the Summative test in the CBL and PjBL classes, it is known that there is no significant difference in learning outcomes for the two classes. However, the scores obtained in both classes were on average High, namely 79, or A- according to the University of Jambi's value scale. This shows that both models, namely CBL and PjBL combined with the use of AI technology, the Chat GPT application is effective in influencing the success of student learning in the Indonesian Language Course, the topic of Writing Scientific Papers. While in terms of student participation there is a significant difference between classes using CBL and PjBL. Based on the analysis, it is known that the average student participation in the CBL class is 71.56%. While the average student participation in the PjBL class is 87.49%. The results of this study strengthen the results of previous studies which show that the use of AI technology combined with the modern learning models CBL and PjBL can increase student participation in the learning process.